2021
DOI: 10.1016/j.isci.2021.103163
|View full text |Cite
|
Sign up to set email alerts
|

Regulated on Activation, Normal T cell Expressed and Secreted (RANTES) drives the resolution of allergic asthma

Abstract: Summary RANTES is implicated in allergic asthma and in T cell-dependent clearance of infection. RANTES receptor family comprises CCR1, CCR3, and CCR5, which are G-protein-coupled receptors consisting of seven transmembrane helices. Infections with respiratory viruses like Rhinovirus cause induction of RANTES production by epithelial cells. Here, we studied the role of RANTES in the peripheral blood mononuclear cells in cohorts of children with and without asthma and validated and extended this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 54 publications
3
5
0
Order By: Relevance
“…Increased RANTES levels have been observed during airway eosinophilia in asthma and COPD patients along with increased nitric oxide synthase (NOS 2 ). 21,22 This is consistent with the NOS 2 activation we observed in upstream regulators in disease network pathway analysis. Further, elevated RANTES expression has been observed in patients with lung adenocarcinoma.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Increased RANTES levels have been observed during airway eosinophilia in asthma and COPD patients along with increased nitric oxide synthase (NOS 2 ). 21,22 This is consistent with the NOS 2 activation we observed in upstream regulators in disease network pathway analysis. Further, elevated RANTES expression has been observed in patients with lung adenocarcinoma.…”
Section: Discussionsupporting
confidence: 88%
“…23,24 RANTES is involved in the recruitment of CD4 lymphocytes and CD4-mediated immune responses via CCR receptors in the adaptive phase. 22,25 Our data suggest that the removal of TPP1 in club cells may have dysregulated this response.…”
Section: Discussionmentioning
confidence: 81%
“…In addition, the proinflammatory role of CCL5 has been challenged in studies in mice in which therapeutic administration of CCL5 contributes to the resolution of allergen-induced asthma by orchestrating the transition from effector GATA-3 1 CD4 1 T cells and inflammatory eosinophils into immunoregulatory type T cells and resident eosinophils, respectively. 6 Finally, although the correlative human data presented may support the findings of Fu et al 5 from mice, whether the IL-9/Arg1/CCL5 pathway contributes to human asthma remains unknown. Future studies to assess these mechanisms in patients receiving anti-IL-9 therapy could potentially provide insight.…”
supporting
confidence: 50%
“…2 A recent study by Fu et al in Science Immunology 5 provides novel insight into the mechanism by which increased IL-9 might contribute to the pathogenesis of asthma. IL-9 is produced by CD4 1 T H 2 and T H 9 subsets, as well as by group 2 innate lymphoid cells (ILC2s) 4,6 (Fig 1). However, the cellular targets and cell-specific roles of IL-9 during type 2 inflammation are not well established.…”
mentioning
confidence: 99%
“…MIP‐1b and RANTES are generally classified as type 2 associated chemokines, known for recruitment of eosinophils, for example, in the airways 33,34 . However, in recent studies, the latter have been suggested to have more pleiotropic capabilities 35 . Moreover, in RV‐affected subjects, RANTES has been associated with bronchial smooth muscle cell chemotaxis, thereby contributing to possible airway remodeling 36 .…”
Section: Discussionmentioning
confidence: 99%